Peran Balanced Scorecard dalam evaluasi kinerja strategis BCA Syariah - Wirayuda, Muhammad Reza (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the role of the Balanced Scorecard (BSC) in evaluating the strategic performance of PT Bank BCA Syariah (BCA Syariah) using a conceptual approach based on maqashid sharia. In facing financial industry competition and digital transformation, BCA Syariah requires a performance measurement system that evaluates not only financial aspects but also non-financial dimensions such as customer satisfaction, internal business processes, and learning and growth. The Balanced Scorecard is considered relevant as it balances financial and spiritual orientations in Islamic banking operations. This study applies a literature review and comparative approach to examine the integration of the four perspectives of the Balanced Scorecard with maqashid sharia principles. The findings indicate that the implementation of the Balanced Scorecard enhances BCA Syariah’s strategic effectiveness through strengthened sharia governance, digital service innovation, and the development of ethical human resources. Thus, the Balanced Scorecard plays a vital role as a strategic evaluation tool that helps BCA Syariah achieve a balance between profitability, sustainability, and sharia compliance.